A fuzzy logic-based frequency control scheme for an isolated AC coupled PV-wind-battery hybrid system. (3rd July 2020) - Das, Somnath; Akella, A. K.
ABSTRACT: The power generation from a renewable energy system has a fluctuating nature due to the intermittent sources. Mismatch between power generation and load demand causes a deviation from the desired frequency in power supply. A frequency control scheme for an isolated PV-wind-battery hybrid energy system is proposed by using fuzzy logic control for automatically select the frequency deviation suppressing element without communications among the different operational controllers. That said, the scheme proposed in this paper requires fewer measuring instruments. The proposed control scheme requires two parameters – system frequency and battery state of charge measurement in order to execute the following tasks. The first task includes – selection of proper frequency balancing element (i.e. battery or a dump load or a primary variable load) that depends on the frequency deviation and battery state of charge. The second task is to address the control operation of the selected element from battery, dump load and primary load. Here, we have demonstrated that by the control scheme, fluctuation of system frequency can be suppressed within an allowable limit owing to effective power management of the hybrid system. The scheme presented here simplifies the integration of renewable energy systems to an existing hybrid power system.